Ecological drought consequences on sustainable development in Iraq - Aliyas , Ibraheem M.; Alrawi, Ayham T; Mohammad, Nadira A (Technium EcoGeoMarine, 2022)
This study is aimed to analyze the spatiotemporal changes of drought in Iraq . Drought is one of the dangerous ecological phenomenon .That earth planet has been suffering since ancient times from ecological challenges such as drought , which have adverse effect on mankind activities and its damages are reflected on sustainable development ; economically , socially and ecologically, where its severity has recently increased. Iraq is considered the fifth country in the world in suffering of drought consequences , therefore, this research was prepared to analyze the ecosystem factors which related with drought, such as weather with a historical dimension at over the past and currently in Iraq through verification about of the weather features such as a temperatures and rainfall over half a century, for the period between 1970 -2020 . Where is proved from spatial analyze , it was the southwest and south region of Iraq are severely affected by drought due to the lack of rainfall and the temperatures rising . This study showed through temporal analyze of weather through the monitoring data in Iraq according to the (SPI), that is referred the warming is rising +2.1degC through 50 past years . Where this rise continues from 1998 until 2020, , with a linear regression of R2 = 0.7084.And there was an anomaly in the average of annual rain fall between 1970-2020. As The results is revealed the reduction of rainfall by [?]84 mm through the past of 50 years ,that precipitation began in decreasing continuously from 1998 until 2020 , with linear regression R2 = 0.1957. This is considering an indicators of climate change , where the drought is one of its repercussion ,which requires adapting with it ,by creating the solutions ,including changing of the mankind systems activities for reducing greenhouse gas emissions by resorting to renewable energies.